2013
DOI: 10.4236/ojcm.2013.32005
|View full text |Cite
|
Sign up to set email alerts
|

A One Pot Green Synthesis and Characterisation of Iron Oxide-Pectin Hybrid Nanocomposite

Abstract: Nano-composites comprised of magnetite nanoparticles in a pectin matrix were prepared by the co-precipitation method. Both sodium hydroxide and ammonium hydroxide were used as precipitating agents and the effects of stoichiometric ratios of iron salts to polymer concentration on particle properties were investigated. The precipitates obtained with NH 4 OH were sponge-like. The XRD pattern revealed magnetite as the only iron oxide phase present when NH 4 OH was used as precipitating base whilst nanoparticles pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 17 publications
2
27
0
2
Order By: Relevance
“…The increased adsorption efficiency of PSMGPB nanocomposites was attributed to the pectinstabilized separation of graphene oxide sheets and the enhanced distribution of magnetites on the graphene oxide surface. The stabilization of graphene oxide sheets using pectin, and the magnetite distribution were reported previously (Devasenathipathy et al, 2014;Ngenefeme et al, 2013;Namanga et al, 2013;Sahu and Dutta, 2011;Zakharova et al, 2012). Additionally, the presence of functional groups, such as hydroxyl (AOH) and carboxyl (ACOOH), from graphene oxide sheets and pectin enables Prussian blue attachment that leads to enhanced adsorption capacity in PSMGPB nanocomposites.…”
Section: Adsorption Experimentsmentioning
confidence: 87%
“…The increased adsorption efficiency of PSMGPB nanocomposites was attributed to the pectinstabilized separation of graphene oxide sheets and the enhanced distribution of magnetites on the graphene oxide surface. The stabilization of graphene oxide sheets using pectin, and the magnetite distribution were reported previously (Devasenathipathy et al, 2014;Ngenefeme et al, 2013;Namanga et al, 2013;Sahu and Dutta, 2011;Zakharova et al, 2012). Additionally, the presence of functional groups, such as hydroxyl (AOH) and carboxyl (ACOOH), from graphene oxide sheets and pectin enables Prussian blue attachment that leads to enhanced adsorption capacity in PSMGPB nanocomposites.…”
Section: Adsorption Experimentsmentioning
confidence: 87%
“…The peaks observed at 3600 cm À1 and 2800 cm À1 were assigned to the hydroxyl and carboxylic hydroxyl groups respectively. The peak observed at 1026 cm À1 is assigned to the glycosidic bonds linking two galacturonic sugar units, while the peak obtained at 1608 cm À1 is assigned to the carbonyl group of the esterified pendant of pectin [22,34]. However, all these peaks were disappeared in the ATR-FTIR spectrum of graphene/pectin-CuNPs which clearly indicating that these functional groups are devoted to accommodate CuNPs.…”
Section: Characterization Of Graphene/pectin-cunpsmentioning
confidence: 68%
“…Previously B. Prasad Rao et al reported that after a gradual loss of water up to 180 °C (10% weight loss), the next phase (250–550 °C) showed 20.21% weight loss form EPS decomposition . Another report has revealed that TGA of pure magnetite exhibited no major change in mass with an increase in temperature, whereas pectin coated magnetite displayed a mass descent between 200 and 350 °C which was due to the decomposition of the pectin coating on the nanoparticles .…”
Section: Resultsmentioning
confidence: 99%
“…Another report has revealed that TGA of pure magnetite exhibited no major change in mass with an increase in temperature, whereas pectin coated magnetite displayed a mass descent between 200 and 350°C which was due to the decomposition of the pectin coating on the nanoparticles [43].…”
Section: Biochemical Testsmentioning
confidence: 98%